2022
DOI: 10.1002/mdc3.13504
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Other Vascular Risk factors' Impact on Non‐Motor Symptoms in Parkinson's Disease

Abstract: Background Previous studies revealed an association between vascular comorbidities and obstructive sleep apnea (OSA) and the severity of motor and cognitive symptoms in Parkinson's disease (PD). However, there is a lack of studies assessing the entire spectrum of non‐motor symptoms (NMS). Objective To investigate the relationship between vascular comorbidities and NMS in PD patients. Methods Patients were assessed at baseline and 4 years later with the Non‐Motor Symptom Assessment Scale, Parkinson's Psychosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Our results are in line with previous studies that failed to demonstrate a link between the occurrence of OSA and more severe neuropsychiatric symptoms [64,65], whereas the absence of a relationship with cognition seems to be in contrast with previous results in both PD [2] and non-PD populations [66][67][68]. It should be noted that the cross-sectional methodology we employed in the present meta-analysis might have affected this result, because a recent study performed by Meira et al [32] Although OSA does not appear to affect patients' QoL, the possible detrimental effect of intermittent hypoxia on the brain, which is already vulnerable to PD degenerative processes, should not be underestimated due to its prevalence and adverse consequences [2,69].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are in line with previous studies that failed to demonstrate a link between the occurrence of OSA and more severe neuropsychiatric symptoms [64,65], whereas the absence of a relationship with cognition seems to be in contrast with previous results in both PD [2] and non-PD populations [66][67][68]. It should be noted that the cross-sectional methodology we employed in the present meta-analysis might have affected this result, because a recent study performed by Meira et al [32] Although OSA does not appear to affect patients' QoL, the possible detrimental effect of intermittent hypoxia on the brain, which is already vulnerable to PD degenerative processes, should not be underestimated due to its prevalence and adverse consequences [2,69].…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the cross‐sectional methodology we employed in the present meta‐analysis might have affected this result, because a recent study performed by Meira et al. [32] provided a positive ES (PD patients with OSA reporting higher scores on global cognitive tests than PD patients without OSA) considering baseline data, whereas they demonstrated a progressive cognitive decline through a follow‐up methodology. Moreover, none of the included studies assessed cognitive functions by using an extensive neuropsychological battery.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…OSA patients with PD exhibit a lower desaturation index, lower mean and nadir oxygen saturation values, and longer time with an oxygen saturation below 90% throughout the night than OSA patients without PD ( 36 , 37 ). Previous studies have shown an association between vascular comorbidities and OSA as well as the severity of motor and cognitive symptoms in PD ( 38 ). However, there is a lack of studies assessing the relationship between OSA and VHs.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, features related to OSA, including intermittent hypoxia and sleep fragmentation, can accelerate the accumulation of β-Amyloid and Tau-proteins in the brain and independently trigger an Alzheimer's-type neuropathology in PD. Longitudinal investigation reported that PD-OSA showed a more severe deterioration, especially of executive functions at the 4-year follow-up (Meira et al, 2022 ). Interestingly, CPAP treatment of OSA in PD improved overall non-motor symptoms and global cognitive functions over a 12-month period (Kaminska et al, 2018 ).…”
mentioning
confidence: 99%